The illearth war - Donaldson, Stephen R. (New York : Holt, Rinehart and Winston, 1977)
Returning to the Land, after forty years of its time, Thomas Covenant finds the powers of evil, under Lord Foul the Despiser, fully unleashed and assumes the responsibility of finding a way to defeat Lord Foul.
An epic fantasy. The second volume of the author's trilogy, the first of which is Lord Foul's bane and the third, The power that preserves.
Keywords: Covenant, Thomas (Fictitious character) -- Fiction; Fantasy fiction